SINIR ELEMANLARI YÖNTEMİ İLE İKİ BOYUTLU POTANSİYEL DAĞILIMININ HESAPLANMASI - GENCER, ALTAN (Fırat Üniveristesi, 2002)
Bu tez çalışmasında, Sınır Elemanları Yöntemi yardımıyla iki boyutlu potansiyel dağılımları hesaplanmıştır. MATLAB yazılımında hazırlanan bir program ile sabit sınır elemanları kullanılarak Laplace denklemi tipindeki çeşitli potansiyel problemleri çözülmüştür. Sınır bilinmeyenleri hesaplandıktan sonra, problem bölgesi ızgara ile bölmelenerek iç noktalardaki potansiyeller hesaplanmıştır.Elde edilen sonuçlar, analitik olarak hesaplanan sonuçlarla karşılaştırılmıştır. Anahtar Kelimeler : Sınır Elemanları Yöntemi, Potansiyel Dağılımı, Laplace Denklemi.

In this thesis study, two dimensional potential distributions using teh Boundary Element Method have been calculated. Various problems of Laplace Equation type have been solved by a computer program developed in MATLAB software package using constant Bounadry Elements. After the Boundary unknowns variable have been calculated, the potantials of interior points have determined by meshing the problem region with grid. The obtained results have been comparent with those results determined from analytical calculations.Key Words : Boundary Element Method, Potential Distribution, Laplace Equation.
Two dimensional potential distribution calculation by boundary element method
Keywords: Elektrik ve Elektronik Mühendisliği; Electrical and Electronics Engineering